2017
DOI: 10.1055/s-0042-122017
|View full text |Cite
|
Sign up to set email alerts
|

A Forefoot Strike Requires the Highest Forces Applied to the Foot Among Foot Strike Patterns

Abstract: Ground reaction force is often used to predict the potential risk of injuries but may not coincide with the forces applied to commonly injured regions of the foot. This study examined the forces applied to the foot, and the associated moment arms made by three foot strike patterns. 10 male runners ran barefoot along a runway at 3.3 m/s using forefoot, midfoot, and rearfoot strikes. The Achilles tendon and ground reaction force moment arms represented the shortest distance between the ankle joint axis and the l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 41 publications
(49 reference statements)
0
11
0
Order By: Relevance
“…1 ). Previous studies reported that a forefoot strike induced a greater negative power of the ankle joint, corresponding plantarflexion moment, and angular displacement, as compared to that of a rearfoot strike 18 23 34 . The present results suggest that runners can change the damage to muscles around the ankle joint by adapting their running technique to change the plantar flexion moment rather than the dorsiflexion angular velocity and duration of the negative power.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…1 ). Previous studies reported that a forefoot strike induced a greater negative power of the ankle joint, corresponding plantarflexion moment, and angular displacement, as compared to that of a rearfoot strike 18 23 34 . The present results suggest that runners can change the damage to muscles around the ankle joint by adapting their running technique to change the plantar flexion moment rather than the dorsiflexion angular velocity and duration of the negative power.…”
Section: Discussionmentioning
confidence: 94%
“…Previous biomechanical studies have reported that mechanical parameters are affected by factors such as the running technique, running speed, type of running shoes, shoe material, and running surface 6 18 33 35 36 . Mechanical parameters are thought to influence acute and chronic training workloads and provide important information for selecting adaptations and preventing injury 14 .…”
Section: Introductionmentioning
confidence: 99%
“…where Fc and Fs represent the cut-off frequency and the sampling frequency, respectively. This equation was used in the previous studies to estimate the cut-off frequencies [3,22,44,45,50,51]. The instances of foot-contact and toe-off were identified when the value of vertical component of the GRF exceeded and fell below 20 N, respectively.…”
Section: Data Reductionmentioning
confidence: 99%
“…Some epidemiological studies showed that 20-79 % of recreational and competition runners experience running-related injuries of the lower extremities [41,42]. Previous biomechanical studies suggested that many factors, such as type of running shoes, shoe material, running surface, running technique, running distance and frequency, affect the risk of running-related injuries [7,22,27,39,46,47,48]. Furthermore, epidemiological studies reported that these factors affect the incidence of running-related injuries [1,13,40].…”
Section: Introductionmentioning
confidence: 99%
“…5,13 In addition, it has been reported that FFS running produces greater GRF due to the longer GRF moment arm than RFS running. 25 In addition to greater GRF, we observed higher fascicle and SEE force in the FFS than the RFS. While FFS running, runners may be required to generate higher GM muscular force to support and move their body forward.…”
Section: Discussionmentioning
confidence: 61%